If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+3)=20+2x
We move all terms to the left:
3(x+3)-(20+2x)=0
We add all the numbers together, and all the variables
3(x+3)-(2x+20)=0
We multiply parentheses
3x-(2x+20)+9=0
We get rid of parentheses
3x-2x-20+9=0
We add all the numbers together, and all the variables
x-11=0
We move all terms containing x to the left, all other terms to the right
x=11
| 5w=65w | | 5p+16=3(4-p) | | 2x-2x=1+0 | | 2(4x–1)=46 | | 3x=−5 | | x-x3=-29 | | –2x=–3 | | 6x-(-11)=7,6 | | 4a=a+6 | | 8y+11=6y-40 | | 2/16=11/x | | 8x+10=5x+45 | | -a+10-9/a=0 | | 3j+10=64 | | 2x2=49 | | 3/2x-(x-2/2)-2=4-4/3x+11/3 | | x^2+12-220=0 | | 4f=96. | | 5m=70. | | O.7x=5.6 | | 4x+4=6x+19 | | 10(x+4)=41+9x | | 10*(11x+5)=-5*(7x+3)-515 | | 13–x=4+2x | | 11*(x-3)=-3*(x+11)-14 | | 7x+9x=100 | | 37=x5-18 | | x5-18=37 | | 18.43=3.99+x | | 10*(10x+11)=-2*(11x-1)-154 | | 10*(10x+11)=-2*(11x-1)-1540 | | 12*(4x-5)=-11*(10x+10)+208 |